1998
DOI: 10.1034/j.1399-3054.1998.1040317.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the plant growth regulator abscisic acid and high osmoticum on the developmental expression of the maize catalase genes

Abstract: The effects of abscisic acid (ABA) and high osmoticum on catalase (Cat) gene expression in maize have been examined. Each Cat gene responds differently to ABA and osmotic stress at different developmental stages and in different tissues. Cat1 transcript accumulates to high levels in developing and germinating embryos, and in leaves. In embryos, Cat2 and Cat3 transcripts are up‐regulated only at very high ABA concentrations during late embryogenesis and in response to various concentrations of ABA in germinatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 0 publications
6
45
0
Order By: Relevance
“…To cope with oxidative stress, plants have evolved several enzymatic and non-enzymatic systems. The channels by which H 2 O 2 mediates the induction of stomata closure, is by inducing the expression of antioxidant genes SOD (Sakamoto et al 1995;Guan and Scandalios 1998a;Bueno et al 1998), and CAT (Guan and Scandalios 1998b;Guan et al 2000), and increase the activities of antioxidative enzymes such as SOD, CAT, guaiacol peroxidase (GPX), ascorbate peroxidase (APX) and glutathione reductase (GR) in plant tissues (Prasad et al 1994;Gong et al 1998;Bellaire et al 2000). SOD reduces superoxide radicals (O 2 -) to H 2 O 2 , CAT reduces H 2 O 2 to water and dioxygen, APX reduces H 2 O 2 to water and monodehydroascorbate, thus preventing the formation of the highly reactive hydroxyl radical (OH) that can cause lipid peroxidation, protein denaturation, and DNA mutations.…”
Section: Discussionmentioning
confidence: 99%
“…To cope with oxidative stress, plants have evolved several enzymatic and non-enzymatic systems. The channels by which H 2 O 2 mediates the induction of stomata closure, is by inducing the expression of antioxidant genes SOD (Sakamoto et al 1995;Guan and Scandalios 1998a;Bueno et al 1998), and CAT (Guan and Scandalios 1998b;Guan et al 2000), and increase the activities of antioxidative enzymes such as SOD, CAT, guaiacol peroxidase (GPX), ascorbate peroxidase (APX) and glutathione reductase (GR) in plant tissues (Prasad et al 1994;Gong et al 1998;Bellaire et al 2000). SOD reduces superoxide radicals (O 2 -) to H 2 O 2 , CAT reduces H 2 O 2 to water and dioxygen, APX reduces H 2 O 2 to water and monodehydroascorbate, thus preventing the formation of the highly reactive hydroxyl radical (OH) that can cause lipid peroxidation, protein denaturation, and DNA mutations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ABA can cause an increased generation of H 2 O 2 (Guan et al 2000, Pei et al 2000, induce the expression of antioxidant genes encoding Cu, Zn-superoxide dismutase (Cu, Zn-SOD) (Sakamoto et al 1995, Guan and Scandalios 1998a, Mn-SOD (Zhu and Scandalios 1994, Bueno et al 1998 and Fe-SOD , and catalase (CAT) (Williamson and Scandalios 1992, Anderson et al 1994, Guan and Scandalios 1998b, Guan et al 2000, and increase the activities of antioxidative enzymes such as SOD, CAT, guaiacol peroxidase (GPX), ascorbate peroxidase (APX) and glutathione reductase (GR) in plant tissues (Anderson et al 1994, Prasad et al 1994a, Bueno et al 1998, Gong et al 1998, Bellaire et al 2000. In addition, ABA can cause the increase of lipid peroxidation expressed as malondialdehyde (MDA) production in plant cells (Bueno et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Only a slight activation could be seen for ABA-treated coleoptiles. Guan and Scandalios (1998) found that Sod 4A transcript was increased under the influence of ABA in young maize leaves. They stated that ABA mediated changes in oxygen free radical levels activated antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…These treatments cause a wide variety of morphological, physiological and biochemical effects. On the molecular level they are manifested as changes in the pattern of gene expression (Skriver and Mundy 1990, Guan and Scandalios 1998, Guan et al 2000. Recent investigations showed that CHF frequently retarded growth and caused yield losses at crop harvest (Fletcher et al 1995, Rengel andWheal 1997).…”
mentioning
confidence: 99%